Computational Analysis of Water/Cu Nano Fluid Dynamic Viscosity using Molecular Dynamic Simulations - Al Khwaji, Abdusalam Imhmed K.; El Shrif, Ali; Sharf, Abdusalam M.; Abdulla, Zulkifly Mohd (Conference On Engineering Science and Technology, 2021)
To enhance thermal management for micro-electric devices, nanofluids become promising working fluids for many thermo-fluid applications. Thermal characteristics of the working fluids can be improved by nano particles additives dispersed in the working fluid such as Cu-nanoparticles in water.  The nanoparticle additives manage to alter thermal and dynamic properties of the working fluids such as the dynamic viscosity which plays an important role in specifying thermal and dynamic behaviour of the working media. In order to understand the effect of modifying the dynamic viscosity of the working media, the effective value of this property must be determined. The molecular dynamic (MD) simulation has been used to estimate the Cu/water nanofluid dynamic viscosity at partial volume fractions of φ=0.0125 % and φ= 0.02478 %, and at working temperatures 293 K, 303 K, 313 K, 323 K and 333 K. The used spherical shape nanoparticles are made up of numbers of 0.3-nm-diameter Cu-atoms. The MD simulation results have been compared to reliable experimental and analytical results. The estimated values of the dynamic viscosity using MD simulations converge very well to the experimental and analytical values of the dynamic viscosity, which reveals the advantages of using MD simulations to determine physical properties of nanofluid working medias and hence to design more efficient working fluids. The RDF shows good results for the SPCE model
Keywords: Cu/water nanofluid; Dynamic viscosity; Risk performance Pipe; Nanofluids; Molecular Dynamics